IMPLEMENTASI PROGRAM KAMIS JAWA DALAM MENINGKATKAN AKHLAKUL KARIMAH PESERTA DIDIK SD PLUS SUNAN AMPEL KOTA KEDIRI - Binti Mar'atus Sholihah; Yuliana Nurul Islami; Fitri Amalia; Benny Prasetiya; Siti Nurkholifah (LPPM STAI Muhammadiyah Probolinggo, 2021)
This study examines the implementation of the Kamis Jawa Program at SD Plus Sunan Ampel Kediri and its impact on improving students' moral character. In the context of rapid globalization and modernization, maintaining local cultural values poses a significant challenge. The Kamis Jawa Program, which integrates Javanese cultural values into the curriculum, aims to develop good character in students and promote cultural preservation. This research used a qualitative method with a case study design, involving observation, interviews, and document studies to collect data. The results indicate that the Kamis Jawa Program positively affects increasing students' understanding and appreciation of Javanese cultural values, such as politeness, cooperation, and gentleness. The program also successfully promotes the formation of good moral character among students, including respectful attitudes, responsibility, and mutual cooperation. Additionally, the program contributes to the preservation of Javanese culture and the development of students' cultural identity amidst globalization influences. This study provides insight that integrating local cultural values into education can be an effective strategy for developing good student character and preserving culture. The implication is that schools in Indonesia and other regions with similar cultural wealth can adopt similar approaches to integrate cultural values into character education, strengthening cultural identity, and promoting tolerance and diversity. Keywords: Kamis Jawa Program, moral character, character education, cultural preservation, globalization, SD Plus Sunan Ampel Kediri.